Perfusion CT Imaging of Brain Tumors: An Overview - Jain, R. (American Journal of Neuroradiology, 2011)
SUMMARY: Perfusion imaging of brain tumors has been performed by using various tracer and nontracer modalities and can provide additional physiologic and hemodynamic information, which is not available with routine morphologic imaging. Tumor vascular perfusion parameters obtained by using CT or MR perfusion have been used for tumor grading, prognosis, and treatment response in addition to differentiating treatment/radiation effects and non-neoplastic lesions from neoplasms. This article is an overview of the utility of PCT for assessment of brain tumors and describes the technique, its advantages, and limitations. BBBblood-brain barrierCBFcerebral blood flowCBVcerebral blood volumeDSCdynamic susceptibility contrastFDG-PETfluorodeoxyglucose–positron-emission tomographyKtransvolume transfer coefficientMRIMR imagingMTTmean transit timeMVCPmicrovascular cellular proliferationMVDmicrovascular densityPCTperfusion CTPSpermeability surface-area productrCBVregional cerebral blood flowROIregion of interestrPSRrelative percentage signal recoverySDF-1stromal derived factor-1TDLtumefactive demyelinating lesionTVAtotal vascular areaVEGFvascular endothelial growth factorWHOWorld Health Organization